Efeitos dos tratamentos térmicos pós-reparo por soldagem na microestrutura e na dureza de superliga 718 em fundidos e forjados - Marinho Junior, Adeir (2017)
The superalloy 718 is utilized in several applications including aircraft engine parts. Such components are typically repaired by welding followed by solution and age heat treatments. However, there’s a tendency of degradation of the material’s microstructure due to the repetitive thermal cycles which are performed below δ phase solution temperature. Therefore, this work’s goal is to evaluate the microstructural evolution of the alloy and its mechanical behavior in regards to such heat treatments. For this purpose, a sample of superalloy 718 material was used, which contains an electron beam weld joint, that unites cast material to forged material, which was analyzed by optical microscopy, scanning electron microscopy, EDS, EBSD and microhardness measurements. Heterogeneous (abnormal) grain growth was observed and dramatic precipitation of δ phase. And a heat treatment above the δ solution temperature range (1052°C/30 min) was conclusive to obtain a more homogeneous microstructure, with the downside of grain growth, although still within acceptable limits.